2019
DOI: 10.1016/j.sapharm.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Can community pharmacy successfully bridge the gap in care for housebound patients?

Abstract: Contributions: AP conceived the study and coordinated and facilitated the data collection. GF and NH were responsible for data entry and data analysis. GF drafted the manuscript. RK coordinated the data analysis and contributed towards the critical revision of all versions of the manuscript. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…Additionally, simply seeing a smile during communication has been reported to increase cerebral blood flow [17]. Further, conversations improve the ability to think and focus, as well as revitalize the psyche; increased activity during visits leads to the maintenance of daily activity [18] and improved mood [19].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, simply seeing a smile during communication has been reported to increase cerebral blood flow [17]. Further, conversations improve the ability to think and focus, as well as revitalize the psyche; increased activity during visits leads to the maintenance of daily activity [18] and improved mood [19].…”
Section: Discussionmentioning
confidence: 99%
“…Social relationships can influence older adults’ quality of life as much as their physical health [ 47 ]. Recent studies have found that community pharmacist intervention can help to prevent social isolation and improve older adult care [ 48 ].…”
Section: Ageing and The Elderlymentioning
confidence: 99%
“…Despite their qualifications and close contact with society, the potential role of pharmacists in promoting active and healthy ageing is neglected in these programs. Their integration into multidisciplinary teams can contribute to the rational use of medicines, improve health literacy, improve the social integration of older adults, and maintain the sustainability of health care systems [ 39 , 48 , 65 ].…”
Section: Ageing and The Elderlymentioning
confidence: 99%
“…Apoteker di komunitas perlu menyediakan pelayanan untuk melaksanakan pemantauan terapi obat setelah pasien pulang dari rumah sakit. Di sisi lain, pasien yang mengalami penyakit kronis membutuhkan pengaturan obat ketika berada di rumah (Kayyali et al, 2019). Berdasarkan kondisi tersebut maka terdapat peluang dan tantangan besar bagi apoteker untuk melakukan terobosan dalam melaksanakan praktik kefarmasiannya.…”
Section: Pendahuluanunclassified